Experiencias de los profesionales de enfermería durante la gestión del cuidado de la salud mental en las personas diagnosticadas con cáncer de mama (2024)
Breast cancer is considered one of the most common cancers in the world and national population, which is why it has been established as a priority in public health, promoting a prevention and early detection process that favors timely treatment. However, there are millions of women and men who have been diagnosed with breast cancer and live with its complications in their daily, family and work lives, involving aspects as relevant as their mental health